Qibla Direction Calculation Methods in Islamic Astronomy References in Indonesia - Reza Akbar; Aslan Aslan; Riza Afrian Mustaqim (AHKAM : Jurnal Ilmu Syariah, 2022)
This research shows that most Islamic astronomy references in Islamic Universities in Indonesia still use the spherical earth concept to explain the qibla  direction.  However,  based  on  modern  astronomy,  the  earth's  shape  is not a perfect sphere but an ellipsoid. In addition, a contradiction occurs in the  conception  of  magnetic  declination  in  determining  the  qibla  direction. This research aims to examine the relevance of Islamic astronomy reference books  with  the  concept  of  geoscience  based  on  the  magnetic  declination formula  and  concept.  This  research  also  examines  the  calculation  methods for qibla direction based on sharia. This library research applies descriptive- analytic  and  normative  approaches  with  the  data  originating  from  various Islamic astronomy references in the digital library of Islamic universities. This research finds that Islamic astronomy references about the qibla direction are not  yet  relevant  to  the  concept  of  geoscience.  Most  of  those  references  still use references astronomy for qibla calculation. There are still some references contradicting the international consensus regarding magnetic declination. In addition, this study reveals that someone who has the ability to determine the qibla direction through the Vincenty formula should use that concept instead of  spherical  trigonometry.  This  is  because  of  skill  (ahliyyah) and sincerity (juhd)  requirements  in  ijtihad;  Shafi'i's  notion  regarding  ikhtilāf in ijtihād for qibla direction; and Islamic jurisprudence principle stating that certainty is not overruled by doubt.Keywords: Islamic  astronomy;  qibla  direction;  spherical  trigonometry; Vincenty's formula; sharia AbstrakPenelitian  ini  berangkat  dari  fakta  bahwa  sebagian  besar  referensi ilmu falak di perguruan tinggi Indonesia masih menggunakan konsep bumi bulat  dalam  menjelaskan  pokok  bahasan  arah  kiblat.  Padahal,  berdasarkan astronomi modern, bentuk bumi tidaklah seperti bola sempurna, melainkan berbentuk elipsoid. Selain itu, terdapat pula pertentangan konsepsi deklinasi magnetik  dalam  persoalan  penentuan  arah  kiblat.  Penelitian  ini  bertujuan untuk mengkaji relevansi referensi ilmu falak terhadap konsep sains kebumian berdasarkan ketepatan penggunaan formula dan konsep deklinasi magnetik, serta juga menelaah penggunaan formula perhitungan arah kiblat berdasarkan kajian syariah. Penelitian ini termasuk penelitian kepustakaaan menggunakan pendekatan deskriptif analitik dan normatif sumber data dari berbagai referensi ilmu falak yang ada di perpustakaan digital perguruan tinggi keagamaan Islam. Berdasarkan penelitian ini, ditemukan bahwa referensi ilmu falak pada pokok bahasan  arah  kiblat  belum  relevan  dengan  konsep  sains  kebumian.  Hal  ini disebabkan sebagian besar referensi tersebut masih menggunakan perhitungan referensi astronomi untuk memecahkan persoalan arah kiblat. Beberapa referensi ilmu  falak  juga  tidak  mengikuti  konsensus  internasional  mengenai  konsep deklinasi magnetik. Selain itu, penelitian ini mengungkapkan bahwa seseorang yang mampu menentukan arah kiblat melalui perhitungan formula Vincenty sebaiknya  menggunakannya  dan  meninggalkan  perhitungan  trigonometri bola.  Hal  ini  disebabkan  beberapa  pertimbangan,  yaitu  pelaksanaan  ijtihād yang mewajibkan kecakapan (ahliyyah) dan kesungguhan (juhd), pandangan Shafi’i  mengenai  penyelesaian  ikhtilāf dalam ijtihād  penentuan  arah  kiblat, dan kaidah ushūl  al-fiqh  yang  menyebutkan  bahwa  keyakinan  tidak  dapat dihilangkan oleh keraguan (shakk).Kata Kunci: ilmu falak; arah kiblat; trigonometri bola; formula Vincenty; syariah